Revitalizing Local Wisdom in Realizing Religious Moderation in Indonesia - Harahap, Syahrin; Harahap, Sholahudin; an-Nadwi, Sorimonang Sori Monang Rangkuti (Institut Agama Islam Negeri Kediri, 2024)
The aim of this research is to analyze the concept of Revitalizing Local Wisdom in Realizing Religious Moderation in Indonesia. The research approach uses qualitative with a case study design. This research was conducted for six months, from January to June 2024 in three cities in Indonesia, namely Nanggroe Aceh Darussalam (NAD), North Sumatra, and Yogyakarta where these three regions can represent ethnic, religious and local wisdom traditions. Data collection techniques through observation, interviews and documentation. Data sources come from religious leaders, traditional leaders and local communities. The data that has been collected is then analyzed using qualitative descriptive analysis techniques which include several stages, namely data collection, data reduction, and drawing conclusions. The research results show that as a diverse country with a diversity of ethnicities, customs, traditions and religions, Indonesia has room to negotiate in dialogue between cultural traditions and the concept of religious moderation. This is realized by revitalizing local wisdom from several regions, such as from (1) Aceh, like Di'iet, Sayam, Suloh and Peusijuk; (2) North Sumatra is known for Kerah and Dalihan Na Tolu, and (3) Yogyakarta is known for Prasaja, Andhap Asor and Tepa Selira. All of the examples of local wisdom above were carried out to build harmony in society and realize the values of Religious Moderation in Indonesia.